Angiotensin-Converting Enzyme Inhibitor Use and Incident Frailty in Women Aged 65 and Older: Prospective Findings from the Women's Health Initiative Observational Study - Gray, Shelly L.; LaCroix, Andrea Z.; Aragaki, Aaron K.; McDermott, Mary; Cochrane, Barbara B.; Kooperberg, Charles L.; Murray, Anne M.; Rodriguez, Beatriz; Black, Henry; Woods, Nancy F. (Journal of the American Geriatrics Society (JAGS), 2009)
OBJECTIVES: To examine the associations between current use, duration, and potency of angiotensin‐converting enzyme (ACE) inhibitors and incident frailty in women aged 65 and older who were not frail at baseline. DESIGN: Data were from the Women's Health Initiative Observational Study (WHI‐OS), a prospective study conducted at 40 U.S. clinical centers. PARTICIPANTS: Women aged 65 to 79 at baseline who were not frail (N=27,378). MEASUREMENTS: Current ACE inhibitor use was ascertained through direct inspection of medicine containers at baseline. Components of frailty were self‐reported low physical function or impaired walking, exhaustion, low physical activity, and unintended weight. Frailty was ascertained through self‐reported and physical measurements data at baseline and 3‐year clinic contacts. RESULTS: By the 3‐year follow‐up, 3,950 (14.4%) women had developed frailty. Current ACE inhibitor use had no association with incident frailty (multivariate adjusted odds ratio=0.96, 95% confidence interval=0.82–1.13). Duration and potency of ACE inhibitor use were also not significantly associated with incident frailty. A similar pattern of results was observed when incident cardiovascular disease events were studied as a separate outcome or when the sample was restricted to subjects with hypertension. CONCLUSION: Overall, incidence of frailty was similar in current ACE inhibitor users and nonusers.